Automatic Generation of Platform Independent Built-in Contract Testers - Lima, Helton S.; Ramalho, Franklin; Machado, Patricia D. L.; Galdino, Everton L. (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2007)
Automatic generation of built-in contract testers that check pairwise interactions between client and server components is presented. Test artifacts are added to development models, i.e., these models are refined towards testing. The refinement is specified by a set of ATL transformation rules that are automatically performed by the ATL-DT tool. We focus on the KobrA development methodology and the Built-In Testing (BIT) method. Therefore, development and testing artifacts are specified by UML diagrams. To make transformation from development to testing models possible, a UML 2 profile for the BIT method is proposed. The overall solution is part of the MoBIT (Model-driven Built-In contract Testers) tool that was fully developed following Model-Driven Engineering (MDE) approaches. A case study is presented to illustrate the problems and solutions addressed.